PENGARUH PENERAPAN MODEL PEMBELAJARAN QUICK ON THE DRAW TERHADAP AKTIVITAS DAN HASIL BELAJAR KIMIA SISWA PADA MATERI HIDROKARBON - antika nova renja; Miterianifa Miterianifa (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
AbstractThis research was a Quasi-experiment with pretest and posttest design instigated by student activity and learning achievement that were still on low category.  It aimed at knowing the effect of using Quick on the Draw learning model toward student activity and chemistry learning achievement.  The subjects of this research were the tenth grade students of classes 5 (control group) and 6 (experimental group) selected through Simple random sampling technique.  Learning activity data were obtained through observation sheet of student learning activity, and learning achievement data were obtained learning achievement test (posttest).  Then, learning activity data were analyzed by using Descriptive statistical and inferential (nonparametric) analysis techniques.  The data of learning achievement were analyzed by using t test at 5% level.  The research findings revealed that (1) there was an effect of using Quick on the Draw learning model toward student learning activity that Zobserved 4.87 was higher than Ztable 1.96, it meant that Ha was accepted; (2) there was an effect of using Quick on the Draw learning model toward student learning achievement that tobserved 2.63 was higher than ttable 2.00, it meant that Ha was accepted.  It showed that Quick on the Draw learning model positively affected student activity and chemistry learning achievement on Hydrocarbon lesson at the tenth grade of State Senior High School 1 Tambang.Keywords: Quick On The Draw Learning Model, Learning Activity, Learning Achievement, Hydrocarbon.